Self-sovereign Identity framework development in compliance with Self sovereign Identity principles using components - Mohammed Shuaib, Salwani Mohd Daud , Shadab Alam (International Journal of Modern Agriculture, 2021)
Digital identity is the need of the hour, but the existing digital identity solutions are susceptible to different malicious attacks and manipulations. Also, these identity solutions can leak the personal identity information (PII) of the users, and users have no control over them. Another issue of the current identity solutions is that no user data is stored in a centralised manner, and users have no control over them, making them vulnerable. A new phenomenon, Self-sovereign identity (SSI), is gaining popularity to provide a secure and reliable identity solution to the users. SSI solutions provide a reliable and secure identity solution based on identity principles. SSI provides a mechanism for the users to control their identity information and give consent for its use. Also, the identity details are stored in a decentralised fashion with the users that help counter the issues of digital identity solutions. This paper highlights the advantages of SSI adaptation, reviews the existing SSI solutions and evaluate them based on SSI principles. Also, it evaluates the SSI components needed for developing SSI frameworks to fully comply with the SSI principles. It further highlights the steps for adopting an SSI ecosystem and discussed various digital identity governing laws to be undertaken by the governments, and highlights SSI applications in different domains.